In Vivo Role of Catalase-Peroxidase in Synechocystis sp. Strain PCC 6803 - Tichy, Martin (American Society for Microbiology, 1999)
The katG gene coding for the only catalase-peroxidase in the cyanobacterium Synechocystis sp. strain PCC 6803 was deleted in this organism. Although the rate of H(2)O(2) decomposition was about 30 times lower in the ΔkatG mutant than in the wild type, the strain had a normal phenotype and its doubling time as well as its resistance to H(2)O(2) and methyl viologen were indistinguishable from those of the wild type. The residual H(2)O(2)-scavenging capacity was more than sufficient to deal with the rate of H(2)O(2) production by the cell, estimated to be less than 1% of the maximum rate of photosynthetic electron transport in vivo. We propose that catalase-peroxidase has a protective role against environmental H(2)O(2) generated by algae or bacteria in the ecosystem (for example, in mats). This protective role is most apparent at a high cell density of the cyanobacterium. The residual H(2)O(2)-scavenging activity in the ΔkatG mutant was a light-dependent peroxidase activity. However, neither glutathione peroxidase nor ascorbate peroxidase accounted for a significant part of this H(2)O(2)-scavenging activity. When a small thiol such as dithiothreitol was added to the medium, the rate of H(2)O(2) decomposition in the ΔkatG mutant increased more than 10-fold, indicating that a thiol-specific peroxidase, for which thioredoxin may be the physiological electron donor, is present. Oxidized thioredoxin is likely to be reduced again by photosynthetic electron transport. Therefore, under laboratory conditions, there are only two enzymatic mechanisms for H(2)O(2) decomposition present in Synechocystis sp. strain PCC 6803. One is catalyzed by a catalase-peroxidase, and the other is catalyzed by thiol-specific peroxidase.